2020
DOI: 10.1183/16000617.0175-2019
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lysate therapy for the prevention of wheezing episodes and asthma exacerbations: a systematic review and meta-analysis

Abstract: Wheezing and asthma are a growing cause of morbidity in children and adults. Treatment is aimed at prevention of disease exacerbations and preservation of lung function. Respiratory viruses are involved in ∼40–60% of exacerbations. Bacterial lysates prevent recurrent respiratory tract infections and might reduce exacerbations. Moreover, immunomodulatory effects have been observed in human and animal studies. Here we aimed to assess the effects of bacterial lysate therapy on preschool wheezing episodes and asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 45 publications
5
40
0
2
Order By: Relevance
“…Previous studies in children showed that bacterial lysates were possibly effective in reducing asthma exacerbations 18,20 . Unfortunately, these studies were not all designed or powered to monitor exacerbation frequency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in children showed that bacterial lysates were possibly effective in reducing asthma exacerbations 18,20 . Unfortunately, these studies were not all designed or powered to monitor exacerbation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc subgroup analyses, with identical outcomes and statistical plan as described above, were performed for patients being adherent to the study protocol (PP) and PPT2 ( N = 42). Rationale of this PPT2 analysis is that bacterial lysate therapy decreases childhood asthma exacerbations, in asthma that often is allergic in origin 17,18,20 . Patients in the PP analysis were either found to be non‐adherent or expressed no interest/time anymore during the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Según la revisión sistemática y metaanálisis publicados recientemente por Geertje Maria de Boer et al el uso de liofilizados bacterianos mostró una disminución de los episodios de sibilancias y exacerbaciones del asma en niños, redujo el uso de antibióticos y duración de sibilancias y produjo un efecto inmunomodulador beneficioso [1]. Esto se correlaciona con el trabajo publicado por Bartkowiak-Emeryk et al en el cuál se evaluaron los efectos inmunológicos del uso de los liofilizados bacterianos polivalentes en una cohorte de niños con asma alérgico.…”
Section: Transferencia En La Práctica De Dra Patricia Solari (Buenos Aires)unclassified